Viabilitas Kultur Sel Fibroblas pada Tiga Macam Susu Sapi UHT Sebagai Media Simpan Gigi Avulsi (In Vitro) - Delvi Fitriani; Endang Asmaningsih; Muhammad Luqman Rahardian (Jurnal Material Kedokteran Gigi, 2013)
Avulsion is defined by tooth out of its socket becaused of trauma. Immediately replantation is the best treatment of avulsed tooth but if it cant be done the tooth should be stored in a media to keep viability of periodontal ligament cell. To determine effectivity differences of three variant of UHT cow milk as storage media for avulsed tooth in preserving living fibroblast cell. This study was experimental research (in vitro) with Randomized Post Test Only Control Group Design. Sample using fibroblast culture cell. First, sample is incubated for 24 hours then divided into three group, those are UHT cow’s milk with dye and flavour ingredient (group I), plain UHT cow’s milk (group II), unbranded UHT cow’s milk (group III) and Eagle’s medium (control). Living fibroblast culture cell in microplate is counted by ELISA reader using MTT Assay and statistically measured with Annova and LSD. There were significantly differences (p<0.005) among group I (95,93%), group II (93,47%) and group III (79,24%) compare with control group. UHT cow’s milk with dye and flavour ingredient is the most effective storage media for avulsed tooth in preserving living fibroblast cell among treatment group